Artificial intelligence: the major role it played in the management of healthcare during COVID-19 pandemic - Tabrez Uz Zaman; Elaf Khalid Alharbi; Aeshah Salem Bawazeer; Ghala Abdullah Algethami; Leen Abdullah Almehmadi; Taif Muhammed Alshareef; Yasmin Awwadh Alotaibi; Hosham Mohammed Osman Karar (IAES International Journal of Artificial Intelligence (IJ-AI), 2023)
The sudden arrival of COVID-19 called for new technologies to manage the healthcare system and to reduce the burden of patients in the hospitals. Artificial intelligence (AI) which involved using computers to model intelligent behavior became an important choice. Various AI applications helped a lot in the management of healthcare and delivering quick medical consultations and various services to a wide variety of patients. These new technological developments had significant roles in detecting the COVID-19 cases, monitoring them, and forecasting for the future. Artificial intelligence is applied to mimic the functional system of human intelligence. AI techniques and applications are also applied in proper examinations, prediction, analyzing, and tracking of the whereabouts of patients and the projected results. It also played a significant role in recognizing and proposing the generation of vaccines to prevent COVID-19. This study is therefore an attempt to understand the major role and use of AI in healthcare institutions by providing urgent decision-making techniques that greatly helped to manage and control the spread of the COVID-19 disease.